1998
DOI: 10.1001/archinte.158.4.397
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Mood and Survival in Seriously Ill Hospitalized Adults

Abstract: Seriously ill patients should be assessed for the presence of depressed mood even if they have not been given a diagnosis of depression. Further study is needed to determine whether interventions aimed at relieving depressed mood may improve prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…11 Cognitive impairment and depressive symptoms may lead to an erosion of the physical skills needed to maintain functional independence and may leave a person less resistant to acute stressors, such as hospitalization, that often accelerate functional dependence in older people. [21][22][23] In participants with baseline ADL dependence, cognitive impairment predicted further loss of ADL function, but depressive symptoms did not predict further functional decline, and, in fact, subjects with depressive symptoms, on average, demonstrated a slight improvement in ADL function, similar to subjects with neither condition. This may reflect fundamental differences in the natural history of cognitive impairment and depressive symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…11 Cognitive impairment and depressive symptoms may lead to an erosion of the physical skills needed to maintain functional independence and may leave a person less resistant to acute stressors, such as hospitalization, that often accelerate functional dependence in older people. [21][22][23] In participants with baseline ADL dependence, cognitive impairment predicted further loss of ADL function, but depressive symptoms did not predict further functional decline, and, in fact, subjects with depressive symptoms, on average, demonstrated a slight improvement in ADL function, similar to subjects with neither condition. This may reflect fundamental differences in the natural history of cognitive impairment and depressive symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Rovner and colleagues (17) found a similarly elevated risk for death in nursing home patients, and Roach and coworkers (34) showed an association between depression and mortality in critically ill adults, mostly with terminal illness. In a study limited to patients hospitalized with myocardial infarction, FrasureSmith and associates (18) reported that patients with major depression were more than three times more likely to die over the subsequent 6 months than patients without depression.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent and predictive validity were demonstrated with other symptoms and patient survival. 57,63,64 Second, the entire depression subscale of the Brief Symptom Inventory (BSI), a common measure in cancer research, 65 is composed entirely of positive and negative affect items similar to those from the CES-D. It has good psychometric properties with norm-based sub-scale scores for the general population 66 and in cancer patients.…”
Section: Comorbid Conditions and Specific Sites Of Primary Cancer Andmentioning
confidence: 99%